Characteristics of Parent – Child Relationships and Adolescent Problem Behavior - Bandzeladze, Tinatin; Safaridze, Salome (Georgian Psychological Journal, 2026)
The patterns of relationships formed between parents and adolescents play a critical role in either the development or prevention of problem behaviors during adolescence. This study aims to explore the relationship between two aspects of positive parenting – unconditional acceptance and positive discipline – and adolescents’ problem behaviors. A qualitative research design was employed, using in-depth interviews with a total of 20 participants: ten adolescents (aged 12–17) and their parents. The interviews explored the patterns of parent–child relationships, parenting styles, and the participants’ perceptions of behavioral difficulties and their contributing factors. The findings suggest that both unconditional acceptance and the use of positive discipline by parents significantly affect adolescents’ behavioral challenges. One notable result highlights the distinct contributions of each parent: positive discipline practices by fathers and unconditional acceptance by mothers appear to be particularly influential in reducing problem behaviors in adolescents. The analysis emphasizes the psychosocial resources that promote adolescent well-being and act as protective factors against risky behaviors. Based on the findings, the study proposes recommendations for professionals in the field of psychological counseling, particularly in work with parents, as well as for educational and preventive programs aimed at reducing adolescent behavioral problems.